2023
DOI: 10.1093/geronb/gbad053
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Learning Multiple Real-World Skills on Cognitive Abilities and Functional Independence in Healthy Older Adults

Abstract: Objectives The natural learning experience from infancy to emerging adulthood, when considerable cognitive and functional growth is observed, mandates learning multiple real-world skills simultaneously. The present studies investigated whether learning multiple real-world skills simultaneously is possible in older adults and also whether it improves both their cognitive abilities (working memory, episodic memory, and cognitive control) and functional independence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Hal ini didukung dengan fakta bahwa kader kesehatan memiliki pengalaman dalam memandikan lansia meskipun belum menerapkan Teknik yang sesuai, namun hal ini membantu kader untuk lebih cepat menerima informasi dari tim pengabdi. Sebuah penelitian menyebutkan bahwa mempelajari keterampilan dunia nyata secara bersamaan pada orang dewasa yang lebih tua meningkatkan kemampuan kognitif (Leanos et al, 2023).…”
Section: Diskusiunclassified
“…Hal ini didukung dengan fakta bahwa kader kesehatan memiliki pengalaman dalam memandikan lansia meskipun belum menerapkan Teknik yang sesuai, namun hal ini membantu kader untuk lebih cepat menerima informasi dari tim pengabdi. Sebuah penelitian menyebutkan bahwa mempelajari keterampilan dunia nyata secara bersamaan pada orang dewasa yang lebih tua meningkatkan kemampuan kognitif (Leanos et al, 2023).…”
Section: Diskusiunclassified
“…The functional level of older people is influenced by a wide range of factors, from chronic disease to socio-economic status. The independence of the older people's daily life; not being dependent on someone to provide personal care and the organisation of the older people home or living environment is associated with healthy aging [5]. However, emergencies brought about by declining physiology may affect functionality.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors affecting the functional level of the individual is surgical procedures [4,6]. A review of the literature has shown that loss of function occurs not only in older people after lower extremity surgery, but also after cardiac, cancer and abdominal surgery [4][5][6][7]. According to Tan et al, the functional level lost after surgery in the older people may become permanent even if the operation site heals.…”
Section: Introductionmentioning
confidence: 99%